2001
DOI: 10.1007/pl00000227
|View full text |Cite
|
Sign up to set email alerts
|

FK506 is superior to methotrexate in therapeutic effects on advanced stage of rat adjuvant-induced arthritis

Abstract: The results show that FK506 is more effective and less toxic than MTX in treating established AIA in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
(22 reference statements)
0
43
1
Order By: Relevance
“…It has been reported that patients with RA are more susceptible to NSAIDs-induced intestinal ulcerogenic lesions than other NSAIDs users. [3][4][5]17) Furthermore, it is well known that IMC has significant gastrointestinal toxicity as its main adverse effect. Therefore, we demonstrate the gastrointestinal toxicity in IMC-administered AA rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that patients with RA are more susceptible to NSAIDs-induced intestinal ulcerogenic lesions than other NSAIDs users. [3][4][5]17) Furthermore, it is well known that IMC has significant gastrointestinal toxicity as its main adverse effect. Therefore, we demonstrate the gastrointestinal toxicity in IMC-administered AA rats.…”
Section: Discussionmentioning
confidence: 99%
“…The adjuvant-induced arthritis (AA) rat is often used for the study of inflammatory pain during the development of AA is assessed by measuring paw volume (paw edema). 16,17) The paw edema in AA rats is observed the two inflammatory stages (primary and secondary inflammation). The primary inflammation starts from the day following the injection of adjuvant into the right hind foot, and the secondary inflammation is observed from 7 d after adjuvant injection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory pain during the development of AA is assessed by measuring paw volume (paw edema). 38,39) Paw edema in AA rats is known to involve two inflammatory stages, primary and secondary inflammation. The primary inflammation starts from the day following the injection of adjuvant into the right hind foot.…”
Section: Gastric and Small Intestinal Ulcerogenic Response To Imc In mentioning
confidence: 99%
“…It is noteworthy that changes in the biological characteristics of AA rats correspond to those that occur in human RA. 3,5,6,38,39) Therefore, AA rats may provide a useful model for studies on the mechanisms of NSAIDs-induced gastrointestinal lesions in RA. It is known that the severity of arthritis in Wistar rats is moderate and occurs with an incidence of only 50-60%.…”
Section: Gastric and Small Intestinal Ulcerogenic Response To Imc In mentioning
confidence: 99%